THE ANALYSIS OF THE NOMINAL RATE OF PROTECTION AND THE NOMINAL RATE OF ASSISTANCE TO SELECTED AGRICULTURAL PRODUCTS: A CASE STUDY OF THE REPUBLIC OF SRPSKA (BOSNIA AND HERZEGOVINA) - Mrdalj, Vesna; Ostojić, ALeksandar; Dimitrijevic , Miloš; Šegrt, Lazo (Economics of Agriculture, 2025)
This paper aimed to estimate the protection of agricultural producers in the Republic of Srpska, Bosnia and Herzegovina, using prices of nine selected products during 2018 – 2023. Two widely recognised indicators were employed: the nominal rate of protection and the nominal rate of assistance. The findings highlight consistent gaps between domestic and EU reference prices, as well as discrepancies and insufficient budget allocation for certain agricultural products. Strong protection was recorded for beef, pig meat, poultry meat and egg producers, while milk and potato protection showed variability. Conversely, wheat, grain maize, and sheep meat were largely unprotected throughout the analysed period. These results suggest that agricultural policy in the Republic of Srpska should prioritise targeted budgetary support, reduce market price disparities and promote productivity-enhancing measures to improve competitiveness and ensure sector sustainability.